2020
DOI: 10.1093/ibd/izaa158
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ulcerative Colitis and Seronegative Inflammatory Spondyloarthritis With Vedolizumab and Tofacitinib

Abstract: The case report describes the benefits of combination therapy with vedolizumab and tofacitinib in a patient with ulcerative colitis and seronegative inflammatory spondyloarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Nine studies totaling 68 patients were treated with a combination of vedolizumab and tofacitinib for the treatment of partially or non-responsive IBD (Tables 2, 3). Several small case reports and case series of vedolizumab and tofacitinib included six UC patients treated for refractory disease and demonstrated 100% clinical improvement without any reported infections [31][32][33][34]. In the case presented by Lee et al, vedolizumab monotherapy was started in a patient not responsive and intolerant to anti-TNF therapy.…”
Section: Vedolizumab and Tofacitinib Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies totaling 68 patients were treated with a combination of vedolizumab and tofacitinib for the treatment of partially or non-responsive IBD (Tables 2, 3). Several small case reports and case series of vedolizumab and tofacitinib included six UC patients treated for refractory disease and demonstrated 100% clinical improvement without any reported infections [31][32][33][34]. In the case presented by Lee et al, vedolizumab monotherapy was started in a patient not responsive and intolerant to anti-TNF therapy.…”
Section: Vedolizumab and Tofacitinib Combination Therapymentioning
confidence: 99%
“…Tofacitinib 5 mg twice daily was added and achieved steroid-free remission as well as an endoscopically normal colon at six months. Withdrawal of vedolizumab was attempted with re-emergence of symptoms 11 weeks after last vedolizumab infusion, however, remission was restored after re-initiation of vedolizumab as DTT [32].…”
Section: Vedolizumab and Tofacitinib Combination Therapymentioning
confidence: 99%
“…In addition, more than 20 case series and reports provide interesting examples of different clinical scenarios45–67 and several retrospective and uncontrolled observations have explored the outcomes of ACT in patients with refractory intestinal disease, concomitant extraintestinal manifestations or IMID (online supplemental table 1).…”
Section: The Current State-of-the-art In Ibdmentioning
confidence: 99%
“…Lee, SD et al (17) identified 19 patients treated with Tofacitinib and biologic agents for refractory Crohn's Disease between 2017 and 2019 and discovered that combining Tofacitinib with biologic agents were effective in achieving clinical and endoscopic improvement in some patients with severe, refractory Crohn's Disease. Lee, JA et al (18) presented a case of a patient with ulcerative colitis and seronegative inflammatory spondyloarthritis who achieved remission with the dual therapy of vedolizumab and Tofacitinib. Dolinger MT et al ( 19) collected data from refractory pediatric inflammatory bowel disease patients receiving dual therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Lee, JA et al. ( 18 ) presented a case of a patient with ulcerative colitis and seronegative inflammatory spondyloarthritis who achieved remission with the dual therapy of vedolizumab and Tofacitinib. Dolinger MT et al.…”
Section: Introductionmentioning
confidence: 99%